PENGEMBANGAN STRATEGI BISNIS RESTORAN SEGMEN ATAS DI YOGYAKARTA DENGAN PENDEKATAN CRITICAL SUCCESS FACTORS - Edouard Aryadi Supriyadi; Wahyu Supartono; Didik Purwadi (Jurnal Teknologi Industri Pertanian, 2020)
Yogyakarta is the right place to run a culinary business because of Yogyakarta's status as a city of culture, education city, and tourist destination, so it requires restaurant facilities, including for the high class segment. The right business strategy is needed to minimize the risk of competing and maximize the advantages of competition. The object of this research was GW restaurants and the comparisons were LD and SS restaurants. This research was aimed at identifying success factors, analyzing the business environment, and developing its business strategy. This research used descriptive-qualitative techniques with Critical Success Factors (CSF) and SWOT approaches. GW restaurants had Critical Success Factors, namely clear concepts, strong customer relationships, cultural interests, managing a competitive environment, good customer relationships, and determining the right location/place. The business environment consisted of internal and external. The development of its business strategy is to improve the quality of employees, improve the quality of its products and innovations, favor specific menus, increase service time, and conduct advertising promotions and expand the network with social media. Keywords: business strategy, critical success factors, restaurant